Episode-wide Maudsley staging in treatment-resistant depression: a longitudinal tertiary-care comparison of dimensional and categorical outcomes - Antoniou, Anastasia; Pappa, Sofia; Dikeos, Dimitrios; Smyrnis, Nikolaos; Mendlevicz, Julien; Serretti, Alessandro; Cleare, Anthony; Ferentinos, Panagiotis (Frontiers in Psychiatry, 2026)
BackgroundUnlike typical categorical definitions of treatment-resistant depression (TRD) based on antidepressant (AD) trial failures, the Maudsley Staging Method (MSM) is a dimensional measure of resistance also rating episode duration, baseline depression severity and failure of augmentation strategies and ECT. However, MSM has not previously been used longitudinally across the full depressive episode, from episode onset to remission. We applied episode-wide MSM (EW-MSM) in patients with Major Depressive Disorder naturalistically followed to remission in a tertiary-care setting and categorized as 1st and 2nd AD trial remitters, TRD remitters and TRD non-remitters (categorical outcomes). The study aimed to investigate clinicodemographic and treatment-related correlates of EW-MSM and categorical outcomes, comparatively assess their predictive value for depression improvement, and explore the discriminative utility of EW-MSM across categorical outcomes.MethodsWe recruited 267 patients. EW-MSM was scored at remission (MADRS ≤ 9 in two consecutive visits), if achieved. Associations of clinicodemographic and treatment-related characteristics with EW-MSM and categorical outcomes were explored in multivariate models. Their comparative predictive value for depression improvement was tested in hierarchical linear regressions. ROC curves assessed EW-MSM discriminative utility across categorical outcomes.ResultsAnalysis focused on 233 remitters (105 1st AD trial remitters, 62 2nd AD trial remitters and 66 TRD remitters). Both EW-MSM and categorical outcomes were associated with baseline severity, obsessive-compulsive disorder comorbidity, episode duration, number of ADs or AD combination. EW-MSM was additionally associated with psychotic features and use of augmentation strategies. EW-MSM was more strongly associated with baseline severity than categorical outcomes (R2 = 0.24 vs. 0.14) and consequently predicted depression improvement to remission more efficiently in hierarchical regressions (ΔR2 = 0.13 vs. 0.05). EW-MSM discriminated well TRD remitters from 1st AD trial remitters (AUC = 0.91, 95% CI = 0.86-0.95) or from early remitters combined (AUC = 0.865, 95% CI = 0.81-0.92) but not among adjacent categories.LimitationsSingle, tertiary-care setting, unavailability of ECT/esketamine and exclusion of patients on psychotherapy (not rated by MSM) limit study generalizability.ConclusionsEW-MSM reflects clinical and treatment intensity aspects of resistance in depression more strongly and comprehensively than categorical outcomes. Therefore, it offers precision for staging and could be used to more efficiently investigate clinical, biological and psychological correlates of resistance.